Multiple migration: Researching the multiple temporalities and spatialities of migration - Justyna Salamońska (University of Warsaw, Centre of Migration Research (CMR), 2017)
This working paper introduces the multiple-migration concept as a tool enabling the study of the multiple temporalities and spatialities of migration. Against a sedentarised understanding of migration, multiple migrants are people who engage in international movements repeatedly and direct this movement at different destination countries. The sequences of these international movements may differ. Multiple migration may involve onward migration from one destination country to another. It can also involve a phase of return to the origin country before going abroad again. Moreover, multiple migration encompasses different geographies (intra- and intercontinental) and temporalities (from temporary to longer-term). In this working paper I position multiple migration within the existing non-permanent migration literature (including incomplete, liquid and step-wise migration and intra-company transfers). The overview of existing studies describing multiple migration (both quantitative and qualitative) provides information about the numbers involved and the social morphology of multiple migrants, and will be used to identify issues to be explored in future studies of multiple migrants.
Keywords: 330; multiple migration; mobilities; temporary migration; incomplete migration; liquid migration